ANALISIS HUBUNGAN ANTARA KARAKTERISTIK USAHA DENGAN KEEFEKTIFAN JARINGAN KOMUNIKASI AGRIBISNIS IKAN HIAS (KASUS DI KABUPATEN BOGOR, JAWA BARAT) - KURNIA SUCI INDRANINGSIH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
The research was designed to comprehend the effectiveness of agribusinesscommunication network of ornamental fish farmers, and correlations of businesscharacteristics to effectiveness of agribusiness communication network. This research wasconducted in July-August, 2001 in sub-districts Ciampea and Parung, Bogor, West Java. Sixtyfarmers were randomly sampled during the survey. The Tau-b Kendall (?) correlationstatistics was used in the data analyses. The results indicated that agribusiness communicationnetwork was not effective, effective only at business aspect. The laborer, and input ownershipwere related to effectiveness of agribusiness communication network.